Taxonomic review of the genus Orybina Snellen, 1895 (Lepidoptera, Pyralidae, Pyralinae), with description of two new species - Qi, Mujie; Sun, Yongling; Li, Houhun (Zootaxa, 2017)
The taxonomy of the eight species and one subspecies of Orybina in the world are reviewed. Among them, O. puerensis Qi & Li, sp. nov. and O. bellatulla Qi & Li, sp. nov. are described as new to science. Photographs of adults, both male and female genitalia and the distribution map of all the species are provided, along with the keys to the described species.